An Orthotopic Implantation Mouse Model of Hepatocellular Carcinoma with Underlying Liver Steatosis - Kasashima, Hiroaki (STAR Protoc, 2020)
This protocol provides the steps required for a mouse liver orthotopic implantation model. The reliable pre-clinical animal models that have similar characteristics to hepatocellular carcinoma (HCC) are a powerful tool to unveil the mechanisms controlling tumor initiation and progression. Here, we describe a syngeneic orthotopic HCC model that recapitulates the role of a host pro-tumorigenic microenvironment by pre-conditioning mouse livers with a high-fat diet (HFD). For complete details on the use and execution of this protocol, please refer to Kudo et al. (2020).